An overview of palm oil biomass for power generation sector decarbonization in Malaysia: Progress, challenges, and prospects - Zamri M.F.M.A.; Milano J.; Shamsuddin A.H.; Roslan M.E.M.; Salleh S.F.; Rahman A.A.; Bahru R.; Fattah I.M.R.; Mahlia T.M.I. (John Wiley and Sons Ltd, 2023)
Biomass; Budget control; Climate change; Coal; Coal fired power plant; Electric power generation; Gas emissions; Gas plants; Greenhouse gases; Milling (machining); Sustainable development; Bio-energy; Coal-fired power stations; Decarbonisation; Energy; Fossil-fuel power plants; Malaysia; Palm oil biomass; Power- generations; Synergetic decarbonization; Synergetics; Fossil fuel power plants